Interleukin (IL)-10 Is Important in the Maintenance of Trabecular and Cortical Bone and Protects Against Western Diet-Induced Disruption in Bone Remodeling in Mice. (7th June 2021) - Perez, Leo; Alake, Sanmi; Price, Payton; Islam, Proapa; Ice, John; Lucas, Edralin; Smith, Brenda
Abstract: Objectives: The purpose of this study was to investigate if consumption of a western diet (WD) exacerbates the effects of loss of function of IL-10, an anti-inflammatory cytokine, on biomarkers of bone metabolism and microarchitecture. Methods: Six-week-old male B6.129P2- Il10 tm1Cgn /J (IL-10 KO) and C57BL/6 mice (WT) were randomized to treatment in a 2 × 2 factorial with diet (AIN-93 control diet CD vs WD) and strain (IL-10 KO vs WT) as factors. Due to potential influence of high fat on intestinal Ca absorption, a WD diet with added Ca (1.2 g/kg) was used. After 12 wks, whole body dual-energy x-ray absorptiometry scans were performed to assess bone density and body composition, and micro-computed x-ray tomography was used to evaluate trabecular and cortical bone microarchitecture in the femur and lumbar vertebra. Serum biomarkers of bone formation, procollagen 1 intact N-terminal propeptide (P1NP), and resorption, c-terminal telopeptide of type I collagen (CTX-1) were assessed. Results: Body weight, but not % body fat, was lower ( P < 0.05) in IL-10 KO mice relative to WT controls. 12 weeks of WD increased ( P < 0.05) body weight and % fat, but the response was not as great in the IL-10 KO mice. Bone mineral density and content were lower in IL-10 KO mice compared to WT, and the WD had no effect on these parameters. The IL-10 KO mice exhibited a decrease in trabecular bone volume, thickness, and number, and an increase in trabecular separation and structure model index compared to WT mice within the femur and vertebrae. The WD had no effect on these trabecular bone parameters. Cortical bone thickness and area were reduced ( P < 0.05) and porosity increased in both the femur and vertebra of IL-10 KO mice relative to their WT counterparts. This strain effect was not altered by the WD. IL-10 KO mice exhibited a significantly lower serum PINP and higher CTX-1 compared to the WT mice. Despite the lack of structural changes in bone after 12 wks, the WD increased ( P < 0.05) CTX-1 and tended to suppress P1NP ( P = 0.051) in the IL-10 KO mice compared to WT. Conclusions: We conclude that IL-10 plays an important role in bone metabolism and maintaining structural properties and in the absence of IL-10, WD negatively affects both osteoclast and osteoblast activity. Further studies are warranted to determine if structural changes occur with longer exposure to WD. Funding Sources: Oklahoma Agricultural Experiment Station.